The economic potential of the African iron-ore tailings: synthesis of magnetite for the removal of trace metals in groundwater—a review - Usman, Usman Abdullahi; Yusoff, Ismail; Raoov, Muggundha; Hodgkinson, Jonathan (Springer Verlag (Germany), 2019)
Africa has the second largest ultimately recoverable resources (URR) of gigaton (Gt) iron (Fe) ore in the world. South Africa is among the countries in the world with high-quality iron ore deposits. The most significant sources of Fe ore in the African continent are hosted by the banded iron ore formation of Precambrian age with high-quality hematite (Fe2O3) bodies. Synthetic magnetite (Fe3O4) nanoparticles (NPs), in recent years, have emerged as novel magnetic NPs with structurally distinct properties because of intensive research efforts by many researchers. They exhibited almost the same chemical and physical properties with naturally occurring Fe3O4, and they have been successfully adopted in removing trace metals from groundwater. For a better understanding of the development of suitable techniques for their application in contaminated groundwater, this paper emphasizes the synthetic methodology, surface modification, coating with porous materials/inorganic clays, functionalized composites, properties, and its ex situ groundwater remediation application. Magnetic separation is the most suitable and cost-effective method for the groundwater remediation of trace metals for both high and lower concentrations. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.